Eléments azotés de la colonne d'eau et de l'interface eau-sédiment du bassin de Marennes-Oléron : influence des cultures d'huîtres - Feuillet-girard, Michelle; Heral, Maurice; Sornin, Jean-marc; Deslous-paoli, Jean-marc; Robert, Jean-michel; Mornet, Francoise; Razet, Daniel (EDP Sciences, 1988)
The respective influences of the sediment and of oyster (Crassostrea gigas) farming on the accumulation and the recycling of different forms of organic and inorganic nitrogen are described. Fluxes of dissolved inorganic and organic forms of nitrogen were studied between the water column, the water overlying the sediment and the pore waters, while for particulate forms the fluxes were studied between suspended material, the "biodeposits" (faeces and pseudofaeces of Crassostrea) and the sediment. The flux of inorganic nitrogen amounts to 10.5 106 g.m(-2). Yr(-1), while that of organic nitrogen is half this figure. The particulate flux is 15.106 g.m(-2).yr(-1). On the other hand, the phytoplanktonic nitrogen accounts for only 6% of the total particulate nitrogen. This confirms the detrital origin of organic matter in this ecosystem. ln the oyster cultivation areas the nitrogen accumulation is 94 g.m(-2) .yr(-1), while in the control zones it amounts to only 15 g.m(-1).yr(-1). The dissolved mineraI nitrogen flux from the sediment is higher under oyster culture (23 g. m(-2). yr (-1) than in the control zones (15 g. m(-2). yr(-1). Thus, oyster cultivation induces an additional fixation of nitrogen amounting to 71 g. m -2. yr -1. Two seasonal processes characterise this ecosystem: a high winter level of nitrates in the water column and their absorption into the sediment, accompanied by a high production of biodeposits; a spring and autumnal release of amnonia from the sediment in the presence of a high level of dissolved organic nitrogen in the water column. L'influence respective du sédiment et des populations d'huîtres cultivées (Crassostrea gigas) sur l'accumulation et le recyclage des différentes formes de l'azote organique et minéral sont précisées. Les flux d'azote minéral et organique des formes dissoutes de la colonne d'eau, des eaux interstitielles et des eaux subjacentes sont étudiés, ainsi que ceux des formes particulaires représentés par les matières en suspension, les biodépôts et le sédiment. Le flux ...